Estilo de vida de pacientes con periodontitis que asisten a las clínicas de la Universidad Antonio Nariño sede Bucaramanga (2022)
Periodontitis is defined as the inflammation of the supporting tissues of the tooth that progressively produces destructive changes built on the loss of the surrounding bone tissue and the periodontal.